Negative serum (1,3) -β-D-glucan has a low power to exclude Pneumocystis jirovecii pneumonia (PJP) in HIV-uninfected patients with positive qPCR - Yuan Huang; Jie Yi; Jing-jing Song; Li-jun Du; Xiao-meng Li; Lin-lin Cheng; Song-xin Yan; Hao-long Li; Yong-mei Liu; Hao-ting Zhan; Ya-ling Dou; Yong-zhe Li (BMC, 2023)
Abstract Objective The current study evaluated the diagnostic performance of serum (1,3)-beta-D Glucan (BDG) in differentiating PJP from P. jirovecii-colonization in HIV-uninfected patients with P. jirovecii PCR-positive results. Methods This was a single-center retrospective study between 2019 and 2021. The diagnosis of PJP was based on the following criteria: detection of P. jirovecii in sputum or BAL specimen by qPCR or microscopy; Meet at least two of the three criteria: (1) have respiratory symptoms of cough and/or dyspnea, hypoxia; (2) typical radiological picture findings; (3) receiving a complete PJP treatment. After exclusion, the participants were divided into derivation and validation cohorts. The derivation cohort defined the cut-off value of serum BDG. Then, it was verified using the validation cohort. Results Two hundred and thirteen HIV-uninfected patients were enrolled, with 159 PJP and 54 P. jirovecii-colonized patients. BDG had outstanding specificity, LR, and PPV for PJP in both the derivation (90.00%, 8.900, and 96.43%) and the validation (91.67%, 9.176, and 96.30%) cohorts at ≥ 117.7 pg/mL. However, it had lower sensitivity and NPV in the derivation cohort (89.01% and 72.97%), which was even lower in the validation cohort (76.47% and 57.89%). Of note, BDG ≥ 117.7 pg/mL has insufficient diagnostic efficacy for PJP in patients with lung cancer, interstitial lung disease (ILD) and nephrotic syndrome. And although lymphocytes, B cells, and CD4+ T cells in PJP patients were significantly lower than those in P. jirovecii-colonized patients, the number and proportion of peripheral blood lymphocytes did not affect the diagnostic efficacy of serum BDG. Conclusions Serum BDG ≥ 117.7 pg/mL could effectively distinguish P. jirovecii-colonization from infection in qPCR-positive HIV-uninfected patients with infectious diseases, solid tumors (excluding lung cancer), autoimmune or inflammatory disorders, and hematological malignancies. Of note, for patients with lung cancer, ILD, and nephrotic diseases, PJP should be cautiously excluded at BDG < 117.7 pg/mL.